Trends in alcohol consumption in middle-aged and older adults, assessed with self-report and the alcohol marker phosphatidylethanol – A longitudinal HUNT study - Kjerstin Tevik; Ragnhild Bergene Skråstad; Jūratė Šaltytė Benth; Geir Selbæk; Sverre Bergh; Olav Spigset; Steinar Krokstad; Anne-Sofie Helvik (PLoS ONE, 2025)
Background Alcohol is a leading risk factor for disease burden. We examined longitudinal trends in sex and age-specific alcohol consumption among middle-aged and older subjects who had participated in the population-based Trøndelag Health Study (HUNT) in Norway since the 1990s. Methods This study included 23,151 individuals aged ≥43 years when they participated in the HUNT2 Survey (1995–1997) and who also had participated in the HUNT3 Survey (2006–2008), and/or the HUNT4 Survey (2017–2019). We used self-reported data to examine trends and identify sex- and age-specific differences in abstinence from alcohol, current drinking, risky drinking (≥8 units of alcohol/week), and heavy episodic drinking (≥5 or ≥6 units of alcohol in one sitting at least monthly). Concentrations of the objective alcohol marker phosphatidylethanol (PEth) were available in subsamples from HUNT3 to HUNT4. Results The proportion of subjects with self-reported alcohol abstinence and with PEth concentrations <0.03 µmol/l increased from HUNT2 and/or HUNT3 to HUNT4, while heavy episodic drinking and PEth concentrations ≥0.03 µmol/l decreased from HUNT3 to HUNT4 in both sexes in most age groups, and more in men than in women. There was an increase in risky drinking from HUNT2 to HUNT4 in women and men aged 43–64 years in HUNT2. Men were more likely to consume alcohol than women measured with both self-report and with PEth in most age groups. Among those aged ≥65 years in HUNT2 a convergence between the sexes regarding abstinence and heavy episodic drinking was observed which was mostly caused by changes in men. Conclusion Drinking patterns among middle-aged and older Norwegians have changed since the 1990s with a trend toward more abstinence and less heavy episodic drinking and PEth concentrations ≥0.03 µmol/l in both women and men with increasing age. There is a trend of more risky drinking with age among both sexes.